Виховання власної гідності у дітей старшого дошкільного віку - Писаренко, Марина Олександрівна (My University, 2025)
Тема кваліфікаційної роботи «Виховання власної гідності у дітей старшого дошкільного віку» досліджувалася на теоретичному та емпіричному рівнях. Результати представлено у двох розділах роботи. На теоретичному рівні схарактеризовано стан розробки проблеми вітчизняними та зарубіжними фахівцями; визначено зміст та структуру провідної категорії; розкрито особливості розвитку власної гідності в дошкільному дитинстві; обґрунтовано педагогічні умови оптимізації процесу виховання досліджуваної якості у ЗДО. З метою розв’язання емпіричних завдань дослідження розроблено програму й методику констатувального експерименту; визначено критерії, показники та структурні компоненти вихованості у дітей 5 7 років власної гідності; описано рівні сформованості даної якості у досліджуваних старшого дошкільного віку; розроблено систему формування власної гідності, обґрунтовано педагогічні умови оптимізації освітнього процесу у ЗДО, розкрито технологію виховання даної моральної якості у дітей 5-7 років.
The topic of the qualification work "Education of self esteem in children of senior preschool age" was studied at the theoretical and empirical levels. The results are presented in two sections of the work. At the theoretical level, the state of development of the problem by domestic and foreign specialists is characterized; the content and structure of the leading category are determined; the features of the development of self esteem in preschool childhood are revealed; pedagogical conditions for optimizing the process of educating the studied quality in preschool education are substantiated. In order to solve the empirical tasks of the study, a program and methodology for a ascertaining experiment have been developed; criteria, indicators and structural components of upbringing in children 5--7 years of self--esteem have been determined; the levels of formation of this quality in the studied children of senior preschool age are described; a system for forming self--esteem has been developed, pedagogical conditions for optimizing the educational process in preschool education are substantiated, and the technology for educating this moral quality in children 5--7 years of age has been revealed. Key words: dignity as a personal phenomenon, a preschooler's own dignity, age dynamics of changes in manifestations of dignity, adequate self--esteem, pedagogical conditions for optimization, educational innovations, creation of a developmental environment.
Keywords: гідність; самооцінка; власна гідність; діти старшого дошкільного віку; виховання гідності